Transformation of Emotional Intelligence Resilience Towards Psychological and Behavioral of Youth - Siti Sarawati Johar; Khairul Azman Mohamad Suhaimy; Khairol Anuar Kamri; Fadillah Ismail; Norizan Rameli; Raja Zirwatul Aida Raja Ibrahim (CV. Literasi Indonesia, 2021)
This article is focused on discussing the importance of strengthening emotional intelligence to achieve more integrated human domains. The discussion is in terms of challenges and resilience of emotional intelligence transformation on the psychological and behavioral impact of youth. Human capital resources among youths are the main thrusts of national development, especially from political, economic, social, and educational aspects. However, the role of youth as agents of change in society would be meaningless if it is a transformation from darkness to brightness, from positive to negative, and from peace to chaos. The important elements that need to be as a knowledgeable youth are not merely intellectual intelligence alone, but also need to have a strong emotional and spiritual intelligence to achieve the positive of emotional, thinking and behavior. Emotional intelligence can be a determining factor in behavior and ideology that is more mature and prosperous among the youth of the country. Therefore, the need to have emotional intelligence is as important as intellectual intelligence to achieve a real balance in life. Positive youth can stand up as a citizen who is full of identity and dare to cope with the competitive world, but also wisely handle whatever challenges. A strong emotional intelligence in the youth can also help transform the country's expectations into reality in the quest for the creation of a first-class human capital.